Use of Social Media among University Students: Leisure or Learning: Fayyaz Ahmad Faize, Fazal ur Rahman, Muhammad Athar Hussain (PJDOL, 2023)
The use of social media, particularly Facebook has grown tremendously popular and is increasing fast with every coming day. Most of the users happen to be students of higher education institutions, so it is pertinent to explore the nature of its use by university students, the harms associated with it and the issue of Facebook for spreading religious posts.